Requirements for the Professional Skills of a Modern Teacher (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2024)
This article provides information on the implementation of the process of teacher training in pedagogical higher educational institutions, and the fact that the state and society have set new requirements for the process of teacher training. The most important task facing the educational system today is to prepare students for future professional activities and educate them as mature staff.